KEDUDUKAN ANAK ANGKAT DALAM HAK WARIS MENURUT KITAB UNDANG–UNDANG HUKUM PERDATA - Adelia Rosalina (Universitas 17 Agustus 1945 Samarinda, 2022)
AbstractAdoption of a child is an act in a legal event that gives birth to a new relationship, namely between the adoptive parents and the adopted child. Adoption of children in Indonesia is a common thing for Indonesian people, not a few of those who are not blessed with children adopt children. The purpose of writing is to find out the procedure for adopting children according to the Civil Code Law and to find out the position of the adopted child in obtaining inheritance rights according to the Civil Law Code. The type of research method used is a normative research method with a statute approach. Data collection techniques were carried out by literature study and data processing was carried out by collecting complete literature. The results of the research and discussion concluded that the adoption procedure can be carried out bymeans of prospective adoptive parents registering their application and then waiting for an email to conduct a trial by presenting the applicant's witnesses to strengthen the information in the adoption process, if accepted, the panel of judges will decide and make a court ruling. . While the position of an adopted child in inheritance rights according to civil law is the same as a biological child/legitimate child, for that he has the right to inherit the inheritance of his adoptive parents according to law or inherit based on testamentary inheritance law if he gets a testament (will grant).